A study of surface wash and runoff at Tekala Forest Reserve Malaysia - Toum, Sabry Al; Othman Jaafar,; Sharifah Mastura S.A, (Journal of Faculty of Social Sciences and Humanities. Universiti Kebangsaan Malaysia, 2005)
The surface wash and runoff study was carried out using closed erosion plots in Tekala Forest Reserve in Hulu Langat, Selangor. Variation on the rate of surface wash and runoff were analysed for different slope gradient and at varying physical and chemical soil characteristic. It was found that silt and fine sand were subjected to higher erosion rate compared to clay and course sand. Content of fine sand and silt in eroded materials increased in the range of 4.8 to 7.0 % and 11.8 to 22.5% respectively. The average reduction of course sand and clay were 8.6% and 16.0% respectively. The average rate of surface wash at study site were 85.0 g m-2 yr-1 . This was relatively higher compared to soil loss in Sarawak of 35.5 g m-2 yr-1 . There was a significant and positive correlation between rates of surface wash and surface runoff with average product moment correlation, r of 0.75. During the study period, seven extreme events with rainfall greater than 50 mm in single storm were recorded. These storms account for 25% of the total rainfall and 29% of the surface wash during the one year study period between 7th August 1994 to 17th August 1995. There were also positive and significant correlation between slope angle and surface wash (0.92) and the surface runoff (0.77).